The Role of the Principal in Implementing the School Driving Program at SMA Negeri 3 Banda Aceh - Fadila, Lisa; Suraiya, Nana; Husna, Asmaul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The principal plays a crucial role in managing and directing various school activities, directly contributing to the success of the school alongside other components, such as teachers and students. This study aims to examine the role of the principal at SMA Negeri 3 Banda Aceh in implementing the School Empowerment Program. The research employs a descriptive qualitative approach with 9 informants as subjects, consisting of the principal, teachers, and students. The research object is the School Empowerment Program at SMA Negeri 3 Banda Aceh. Data collection was conducted through interviews and documentation, while data analysis included data reduction, data presentation, and conclusion drawing. The results of the study show that the principal of SMA Negeri 3 Banda Aceh has successfully implemented various interventions in the School Empowerment Program, such as consultative-asymmetric mentoring, strengthening human resources, learning with a new paradigm, data-driven planning, and school digitization. The principal plays an essential role in facilitating the learning committee's understanding of the implementation of the Merdeka Curriculum, leading the development of the operational curriculum, mentoring and evaluating teachers, fostering a culture of reflection, and organizing and evaluating learning communities within the school. This study concludes that the success of the School Empowerment Program heavily relies on the principal's ability to lead effectively, manage change, and implement policies and practices that support school performance improvement.